Pemodelan Karakteristik Kebutuhan Parkir Pada Perhotelan Di Kota Manado - Manabung, Helmut; Rompis, Semuel Y. R.; Timboeleng, James A. (JURNAL ILMIAH MEDIA ENGINEERING, 2017)
The development of tourism industry in Manado City in 2017 along with the growth of supporting facilities in meeting the development of the tourism industry one of the hotel development. As one of the supporting facilities built hotels must have criteria - criteria that can meet the needs of visitors or residents. Parking criteria are important in the transportation system within the hotel area and give effect to the transportation system outside the hotel area. In general, one of the causes of reduced road capacity is parking of vehicles using the road as parking lot of vehicles / on street parking. In order to avoid the occurrence of this congestion is expected that in certain places such as shopping centers, schools / campuses, economic activity centers and others there must be provide with parking place (off street parking) so as to minimize disruption to the capacity of roads. The construction of hotels in the city of Manado had generate   large enough of trip generation from various regions to enter this region. The trip generation or attraction movement that occurs can be such that of the trip generation of people and the trip generation of motor vehicles. The magnitude of these trip generation would causes the need of  the  adequate parking facilities so that the traffic flow which quite busy in the area  of Boulevard and  Jendral Sudirman street will not be disturbed. That is why the knowledge is needed about the characteristics of parking requirements for the existing hotel areas.                The aims of this research were to  provide characteristics of parking needs in some existing hotels in Manado City and to know parameters that affect the parking needs of some hotels in Manado City, so that it can be used as a future approach to resolve the problem of disruption in the capacity of roads.                  Methods used in this study were consist of literature study, primary data collection, secondary data collection and forecasting model using linear regression equation.Results of data analysis revealed that: (1).The regression equation of the car parking requirement with the parameters of the hotels with the best r2 accuracy and qualified statistical testing is the need for car parking which is related to the number of employees and the number of meeting rooms. The standard in the form of regression equation is Y = 1.562 . X0.678 r2=0,841; (2). Based on the analysis with multiple regression the relationship of hotel parameters to the needs of the car park is the number of meeting room, the number of employees and the occupancy rate of the hotel. With the equation as follows: Y = - 56,005 - 4,571 x1 + 0.331 x2 + 1,066 x3, with r2 = 0.999. (3). The number of rooms in the hotel proved to have a large influence on the needs of motor parking at this hotel is indicated by the largest correlation test results among other independent variables, where the relationship between the needs of motor parking with the number of rooms indicated by the equation as follow: Y = - 56,005 - 4,571 x1 + 0.331 x2 + 1,066 x3 ; r2 = 0.993.   Keywords: parking characteristics, disruption, reduced road capacity, trip generation, multiple-regression